Wealth in the 21st century: opportunities for the future - G. M. Berdykulova; M. Abdinova; T. V. Ananiev (Экономика: стратегия и практика)
The article is devoted to economic category “wealth” in order to understand the necessity to use the fundamental basis, experience of advanced countries, unique opportunities in the development of intangible assets and intellectual property as new sources of socio-economic development of a person, enterprise and world nations including Kazakhstan. The goal of the manuscript is to determine ways of a nation and human wealth creation under the new environment of the Fourth technological revolution. To reach the purpose the analysis of theoretical states in the field, clarification the content of the category “wealth” in modern literature, the methodology for estimating the world wealth, classification of world countries by the level of wealth per capita, the place of Kazakhstan in the international welfare ranking have been shown. Characteristics of the financial well-being of the population, the structure of income in the Republic of Kazakhstan, the role of knowledge in the post-industrial society, nowadays transformation into the factor of production and practical application have been revealed. Correlation of tangible and intangible assets, types of intellectual property for capitalization, the human and social capital in the system of human wellbeing have been proved. The practical and theoretical value of the research described in the article consists in classifying sources of wealth according to existing methodologies, identifying new sources determined by the capabilities of the Internet, computer and digital technologies of post-industrial society.